The Influence of Knowledge, Attitudes and Family Support on Patient Adherence in Carrying Out Diet Therapy of Coronary Heart Disease in Outpatient Installation Putri Hijau Hospital - Lajayatri, Fina (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
This study aims to determine the effect of knowledge, attitudes, and family support on patient compliance in carrying out diet therapy in CHD in the outpatient installation of the green field hospital in Medan. This research method is an analytical study using a cross sectional design approach. Data collection techniques used are using questionnaires. The study sample was CHD patients who visited 96 outpatients. The results showed that the majority of patients had good knowledge. Of the majority of patients who have this good knowledge, most of them are also obedient to the diet they run. For the attitude factor it was found that the majority of patients had a good attitude. Of the majority of patients with this good attitude, most of them are also compliant with the diet they run. Then from family support factors it was found that the majority of patients received family support. Of the majority of patients who get family support most of them are also obedient to the diet they run. Based on the statistical analysis, it shows that the value of multivariate logistic regression analysis results on knowledge variables (p = 0.001 <0.05), attitude (p = 0.002 <0.05), and family support (p = 0.000 <0.05) that means there is an influence between knowledge, attitudes, and family support for patient compliance in carrying out diet therapy in CHD